International Court Justice ruling for Palestine-Israel in Indonesian media: Discourse analysis in Kompas.com, CNNIndonesia.com, and Detik.com - Nuraini, Fira Pujia; Mulyana, Deddy; Herawati, Maimon; Shaharoun, Awaluddin (Islamic Communication Journal, 2025)
This research analyzes the coverage of three major media in Indonesia, Kompas.com, CNNIndonesia.com, and Detik.com, regarding the ruling of the International Court of Justice in July 2024, which declared Israel's occupation of the Palestinian territories as illegal. Using a critical discourse analysis approach from Teun A. van Dijk, the research aims to reveal how these media report the ICJ ruling and represent their support for Palestine. Van Dijk's approach focuses on the relationship between discourse, power, and ideology, analyzing the news text's macrostructure (main themes and topics) and micro (choice of words, sentences, and rhetoric). Data were collected from articles published by Kompas.com, CNNIndonesia.com, and Detik.com following the ICJ ruling on 19 July 2024. The findings show that the three media support the ICJ ruling and strengthen the pro-Palestine narrative in Indonesia. Practically, the results of this research can be a reference for developing more effective media communication strategies in supporting international justice issues and building public solidarity. ***** Penelitian ini menganalisis pemberitaan tiga media utama di Indonesia, yaitu Kompas.com, CNNIndonesia.com, dan Detik.com, tentang putusan Mahkamah Internasional (International Court of Justice) pada Juli 2024 yang menetapkan pendudukan Israel di wilayah Palestina sebagai ilegal. Menggunakan pendekatan analisis wacana kritis dari Teun A. van Dijk, penelitian ini bertujuan untuk mengungkap bagaimana media-media tersebut memberitakan putusan ICJ dan merepresentasikan dukungan terhadap Palestina. Pendekatan van Dijk berfokus pada hubungan antara wacana, kekuasaan, dan ideologi, dengan analisis pada struktur makro (tema dan topik utama) serta mikro (pilihan kata, kalimat, dan retorika) dalam teks berita. Data dikumpulkan dari artikel-artikel yang diterbitkan oleh Kompas.com, CNNIndonesia.com, dan Detik.com setelah putusan ICJ pada 19 Juli 2024.  Hasil penelitian menunjukkan bahwa ketiga media tersebut mendukung putusan ICJ dan memperkuat narasi pro-Palestina di Indonesia. Secara praktis, hasil penelitian ini dapat menjadi referensi bagi pengembangan strategi komunikasi media yang lebih efektif dalam mendukung isu keadilan internasional dan membangun solidaritas publik.